Bage Wassele’s Accounting Model: Tradition to Sustainability - Suwandi Suwandi; Darmawansah Darmawansah (Economics and Digital Business Review, 2023)
Accounting in the current era has highlighted broader areas related to social and cultural sustainability in community activities and life. One of the community habits that is in the spotlight is the practice of bage wassele' in cultivating gardens. This ethnographic research aims to uncover the accounting practice of bage wassele' as a supporting pillar for the sustainability of garden cultivation in Awo Village, Lasusua District, North Kolaka Regency. Research data was collected using the interview method. The subjects of this research involved 4 planters as informants who were selected using purposive sampling. Data analysis was carried out using descriptive qualitative analysis techniques with descriptive, reduction and selection stages of research data. The results of the research suggest that bage wassele' accounting practices in cultivating gardens have a positive impact in supporting the economic, social and cultural sustainability of society, by including fair distribution of business results, reduction of social and economic disparities, greater social accountability, sustainable innovation, and decision making that considers profitability, social welfare, and cultural preservation. Furthermore, the practice of bage wassele' helps support the achievement of the SDGs by strengthening the values of justice, cooperation and inclusion, as well as reducing economic inequality, creating economic opportunities and wise management of natural resources to achieve sustainable economic development.